2017
DOI: 10.3389/fimmu.2017.01383
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Ligands and Interferon-γ Synergize for Induction of Antitumor M1 Macrophages

Abstract: Tumor-associated macrophages may either promote or suppress tumor growth depending on their activation status. Interferon-γ (IFN-γ) has been identified as a key factor for inducing tumoricidal M1 phenotype in macrophages. However, it remains unclear whether IFN-γ is sufficient or if additional stimuli are required. Here, we tested IFN-γ and a panel of toll-like receptor (TLR) agonists for the ability to activate murine macrophages toward a tumoricidal M1 phenotype. The following TLR ligands were used: TLR1/TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 82 publications
7
135
0
3
Order By: Relevance
“…Polarization was done on adherent macrophages (1 × 10 6 ) with 100 ng/mL IFN-γ or IL4 + IL13 (25 ng/ml each) for 24 h. Cells thus polarized (and with a non-treated control) were used for flow cytometry, respiratory burst, quantitative polymerase chain reaction (qPCR), and cytometric bead arrays. While LPS + IFN-γ is often used together for M1 polarization (10), and synergize in cytotoxicity assays (37,38), we found that a 24 h incubation with IFN-γ was sufficient to M1 polarize (Tables 2-4), with the addition of LPS not significantly enhancing the IFN-γ responses for either cytokine release nor phagocytic rate (Supplemental Figure 1). As cytotoxicity assays are done on the order of days, it may be that feedback and/or gene regulation that occurs in that timeframe contributes to synergy.…”
Section: Macrophage Polarizationmentioning
confidence: 86%
“…Polarization was done on adherent macrophages (1 × 10 6 ) with 100 ng/mL IFN-γ or IL4 + IL13 (25 ng/ml each) for 24 h. Cells thus polarized (and with a non-treated control) were used for flow cytometry, respiratory burst, quantitative polymerase chain reaction (qPCR), and cytometric bead arrays. While LPS + IFN-γ is often used together for M1 polarization (10), and synergize in cytotoxicity assays (37,38), we found that a 24 h incubation with IFN-γ was sufficient to M1 polarize (Tables 2-4), with the addition of LPS not significantly enhancing the IFN-γ responses for either cytokine release nor phagocytic rate (Supplemental Figure 1). As cytotoxicity assays are done on the order of days, it may be that feedback and/or gene regulation that occurs in that timeframe contributes to synergy.…”
Section: Macrophage Polarizationmentioning
confidence: 86%
“…As most studies looked at APCs, especially DCs, and as gene modulation appears to be cell‐dependent, it is possible that purified macrophages behave differently. The cytokine network is also important; in fact Muller et al reported that the response to various TLR ligands differed if specific additional cytokines, primarily, IFNγ was available to macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…As most studies looked at APCs, especially DCs, and as gene modulation appears to be cell-dependent, it is possible that purified macrophages behave differently. The cytokine network is also important; in fact Muller et al reported that the response to various TLR ligands differed if specific additional cytokines, primarily, IFNγ was available to macrophages [41]. Previous studies reported that the potential antitumoral effects of TLR agonists were mediated through activation of innate immunity, as well as by increased recruitment of T-cells within tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of action of Imiquimod is not yet understood. However, there is evidence, that TLR activation in combination with a second pro-inflammatory signal can transform macrophages towards the anti-tumoral M1 type [75].…”
Section: Possible Therapeutic Implications For Oral Leukoplakiamentioning
confidence: 99%